Magnetic Resonance Imaging of Sacroiliitis in Patients with Spondyloarthritis: Correlation with Anatomy and Histology - Hermann, K.-G. A.; Bollow, M. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Magnetic resonance imaging (MRI) of the sacroiliac joints (SIJs) has become established as a valuable modality for the early diagnosis of sacroiliitis in patients with inconclusive radiographic findings. Positive MRI findings have the same significance as a positive test for HLA-B27. Sacroiliitis is one of the key features of axial spondyloarthritis (SpA) in the classification proposed by the Assessments in Ankylosing Spondylitis (ASAS) group. Early signs of sacroiliitis include enthesitis of articular fibrocartilage, capsulitis, and osteitis. In more advanced disease, structural (chronic) lesions will be visible, including periarticular fatty deposition, erosions, subchondral sclerosis, and transarticular bone buds and bridges. In this article we describe magnetic resonance (MR) findings and provide histologic biopsy specimens of the respective disease stages. The predominant histologic feature of early and active sacroiliitis is the destruction of cartilage and bone by proliferations consisting of fibroblasts and fibrocytes, T-cells, and macrophages. Advanced sacroiliitis is characterized by new bone formation with enclosed cartilaginous islands and residual cellular infiltrations, which may ultimately lead to complete ankylosis. Knowledge of the morphologic appearance of the sacroiliac joints and their abnormal microscopic and gross anatomy is helpful in correctly interpreting MR findings.Citation Format:• Hermann KGA, Bollow M. Magnetic Resonance Imaging of Sacroiliitis in Patients with Spondyloarthritis: Correlation with Anatomy and Histology. Fortschr Röntgenstr 2014; 186: 230 – 237
Keywords: skeletal-axial; MR imaging; inflammation; arthritides